1983
DOI: 10.1159/000265237
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor and Serum IgE Antibody in Experimental Ocular Onchocerca Infection of Guinea Pigs

Abstract: Infection of inbred Strain 2 guinea pigs by subcutaneous or intradermal injection of fresh or cryopreserved living Onchocerca lienalis microfilariae, followed by a challenge intracorneal infection of microfilariae, resulted in serum and aqueous IgE antibody and in significant corneal inflammation. Systemic or intraocular infections given separately were not sufficient to elicit IgE antibody or ocular inflammation. When intravenous transfer of pooled spleen cell suspensions from systemically infected donors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In previous studies, administration of DEC-C to guinea pigs injected intracorneally with O. lienalis Mf increased the severity of the ocu lar lesions, and also increased their IgE anti body responses [9,10]. In the present study DEC-C was given after subconjunctivally in jected Mf had penetrated the central corneal stroma.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In previous studies, administration of DEC-C to guinea pigs injected intracorneally with O. lienalis Mf increased the severity of the ocu lar lesions, and also increased their IgE anti body responses [9,10]. In the present study DEC-C was given after subconjunctivally in jected Mf had penetrated the central corneal stroma.…”
Section: Discussionsupporting
confidence: 49%
“…Microfilariae (Mf) of O. lienalis were obtained from the umbilical skin of cattle and cryopreserved as previously described [9,10]. Cryopreserved Mf were thawed in Hanks' balanced salt solution (HBSS) with 20% fetal bovine serum (FBS), and washed 3 times in HBSS without FBS, containing penicillin (100 U/ml), streptomycin (100 pg/ml) and amphotericin B (4.5 pg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have independently demonstrated a requirement for antigen-specific T cells in the development of onchocercal keratitis. Donnelly et al showed that guinea pigs develop ocular disease characterized by limbitis, corneal inflammation, and peripheral corneal neovascularization after intracorneal inoculation of the cattle parasite O. lienalis (16,17). These workers clearly demonstrated that the inflammatory response and the severity of keratitis is greatly exacerbated if the animals are sensitized prior to ocular challenge, thereby implying a role for specific immunity.…”
Section: Experimental Animal Modelsmentioning
confidence: 99%
“…The concurrent death of many microfilariae during diethylcarbazamine treatment may liberate greater quantities of soluble antigens than would be released during the normal turnover of microfilariae. This is supported by the 30 to 100 per cent increase in circulating immune complexes occurring during diethylcarbamazine treatment of humans with onchocerciasis, and by the increased aqueous and serum antibody following treatment of guinea pigs experimentally infected with 0 lienalis microfilariae (Donnelly, Rockey, Bianco and Soulsby 1983).…”
Section: Discussionmentioning
confidence: 92%